Inositol adenophostin: convergent synthesis of a potent agonist of D-myo-inositol 1,4,5-trisphosphate receptors - Su, X; Dohle, W; Mills, S; Potter, B (American Chemical Society, 2020)
D-myo-Inositol 1,4,5-trisphosphate receptors (IP3Rs) are Ca2+ channels activated by the intracellular messenger inositol 1,4,5-trisphosphate (IP3, 1). The glyconucleotide adenophostin A (AdA, 2) is a potent agonist of IP3Rs. A recent synthesis of D-chiro-inositol adenophostin (InsAdA, 5) employed suitably- protected chiral building blocks and replaced the d-glucose core by d-chiro-inositol. An alternative approach to fully chiral material is now reported using intrinsic sugar chirality to avoid early isomer resolution, involving the coupling of a protected and activated racemic myo-inositol derivative to a D-ribose derivative. Diastereoisomer separation was achieved after trans-isopropylidene group removal, and the absolute ribose-inositol conjugate stereochemistry assigned with reference to the earlier synthesis. Optimization of stannylene-mediated regiospecific benzylation was explored using the model 1,2-O-isopropylidene-3,6-di-O-benzyl-myo-inositol and conditions successfully transferred to one conjugate diastereoisomer with 3:1 selectivity. However, only roughly 1:1 regiospecificity was achieved on the required diastereoisomer. The regioisomers were successfully separated and transformed subsequently to InsAdA after amination, pan-phosphorylation, and deprotection. InsAdA from this synthetic route bound with greater affinity than AdA to IP3R1 and was more potent in releasing Ca2+ from intracellular stores through IP3Rs. It is the most potent full agonist of IP3R1 and was equipotent with material from the fully chiral synthetic route.